1989
DOI: 10.1002/pssb.2221520220
|View full text |Cite
|
Sign up to set email alerts
|

Observation by ESR of electrons localized at intrinsic shallow traps in silver halide systems

Abstract: Electrons shallowly trapped a t intrinsic sites in single-crystal and polycrystalline samples of AgBr, AgCl, and mixed iodohalides are observed by ESR. The results are consistent with a model in which the electron is localised by a silver ion in an effective mass state. The observed ESR linewidths are explained in terms of exchange narrowing. The effect of iodide on the free or nearly-free electron g-value is determined. Addition of iodide to AgCl or AgBr resulted in alloy line broadening. The amount of shallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…It was suggested that the intrinsic binding core consists of an interstitial silver ion [5], but other models include a substitutional silver ion at a surface kink or an internal jog [2]. The intrinsic shallow electron centers have also been observed by EPR spectroscopy and they give an isotrupic, structureless line at g -1.88 in AgC1 [6] and g -1.49 in AgBr [7]. Until now, both optical and EPR spectroscopy have been unable to establish the structure of the binding core.…”
Section: Structure Of the Intrinsic Shallow Electron Center In Agcl Smentioning
confidence: 97%
See 1 more Smart Citation
“…It was suggested that the intrinsic binding core consists of an interstitial silver ion [5], but other models include a substitutional silver ion at a surface kink or an internal jog [2]. The intrinsic shallow electron centers have also been observed by EPR spectroscopy and they give an isotrupic, structureless line at g -1.88 in AgC1 [6] and g -1.49 in AgBr [7]. Until now, both optical and EPR spectroscopy have been unable to establish the structure of the binding core.…”
Section: Structure Of the Intrinsic Shallow Electron Center In Agcl Smentioning
confidence: 97%
“…The ENDOR transitions of silver nuclei are shown in Fig. 1(a) where the nuclear Zeeman frequencies of ' Ag (I = 1/2, 52%) and '" Ag (I = 1/2, 48%) are observable as dips at 6.224 and 7.156 MHz, respectively. Figure 1(b) shows the chlorine ENDOR transitions and the dips at 12.537 and 15.057 MHz indicate the nuclear Zeeman frequencies of 35C1 (I = 3/2, 76%) and 37Cl (I = 3/2, 24%), respectively.…”
Section: Structure Of the Intrinsic Shallow Electron Center In Agcl Smentioning
confidence: 99%
“…The further enlargement of silver clusters can be understood to occur through transport of the mobile photoelectrons and interstitial silver ions and accumulation at one or at most a few growing centers. ESR experiments have also shown evidence for electron trapping in effective mass states that were extended lattice dislocations that penetrated the surface. Microwave photoconductivity experiments showed rapid electron trapping at sites thought to be surface kinks on a time scale of 10 ns at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…18 Thus, the reduction and enhancement of the PC signal in the annealed and deformed crystal, respectively, can be explained in terms of the increased or decreased number of interstitial silver ions.…”
Section: Discussionmentioning
confidence: 99%